2013
DOI: 10.1038/jcbfm.2013.178
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral Pressure–Flow Relationship in Lowlanders and Natives at High Altitude

Abstract: We investigated if dynamic cerebral pressure-flow relationships in lowlanders are altered at high altitude (HA), differ in HA natives and after return to sea level (SL). Lowlanders were tested at SL (n ¼ 16), arrival to 5,050 m, after 2-week acclimatization (with and without end-tidal PO 2 normalization), and upon SL return. High-altitude natives (n ¼ 16) were tested at 5,050 m. Testing sessions involved resting spontaneous and driven (squat-stand maneuvers at very low (VLF, 0.05 Hz) and low (LF, 0.10 Hz) freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 39 publications
(102 reference statements)
4
21
1
Order By: Relevance
“…The phase and gain findings associated with the elevated coherence during the driven oscillations revealed a similar mechanism, namely that gain was lower in the highlanders with the lowest values observed in CMS+. Lower gain is consistent with findings in Himalayan Sherpas (Smirl et al 2014) and may reflect an improved ability to buffer perfusion during rapid alterations in BP to protect against vasogenic oedema in the face of exaggerated OXINOS. However, it would seem unlikely that this constitutes a functionally neuroprotective adaptation given that our participants, in particular CMS+, exhibited clinical signs of neurodegeneration (see below).…”
Section: Haemodynamic Functionsupporting
confidence: 84%
“…The phase and gain findings associated with the elevated coherence during the driven oscillations revealed a similar mechanism, namely that gain was lower in the highlanders with the lowest values observed in CMS+. Lower gain is consistent with findings in Himalayan Sherpas (Smirl et al 2014) and may reflect an improved ability to buffer perfusion during rapid alterations in BP to protect against vasogenic oedema in the face of exaggerated OXINOS. However, it would seem unlikely that this constitutes a functionally neuroprotective adaptation given that our participants, in particular CMS+, exhibited clinical signs of neurodegeneration (see below).…”
Section: Haemodynamic Functionsupporting
confidence: 84%
“…All participants provided written informed consent before participation in this study. This study was part of a larger research expedition conducted in April-June 2012 Lewis et al 2014;Smirl et al 2014;Smith et al 2014;Willie et al 2014Willie et al , 2015Stembridge et al 2015). As such, participants took part in a number of studies conducted in Kelowna, BC Canada (344 m) and during 3 weeks at the Ev-K2-CNR Pyramid Laboratory located near Mt Everest base camp at 5050 m. Participants involved in this study had a minimum of 48 h between studies to mitigate any concern of cross-contamination from pharmaceutical interventions.…”
Section: Methodsmentioning
confidence: 99%
“…There are three major limitations to these previous studies: (a) only the short-term effects of CA during exercise or within 60 min of exercise cessation were examined; the duration of dynamic CA alterations postexercise remain unknown; (b) only two studies have examined the CA relationship across the cardiac cycle (Ogoh, Fadel, et al, 2005;Ogoh, Fisher, et al, 2007); as recent research has shown each phase of the cardiac cycle responds differently to a given stimulus, examining the mean may not accurately portray important subtleties between diastolic and systolic components (Smirl, Wright, Ainslie, Tzeng, & Donkelaar, 2018;; and (c) only one of these prior studies employed a research method (oscillatory lower body negative pressure during the exercise intervention) which evoked sufficient coherence to provide reproducible interpretations of the associated phase and gain metrics (Smirl, Hoffman, Tzeng, Hansen, & Ainslie, 2015). Moreover, recent research has demonstrated when squatstand maneuvers are employed to quantify CA parameters, coherence values are enhanced to near linear levels (~0.99) (Kostoglou et al, 2016;Smirl, Haykowsky, et al, 2014;Smirl et al, 2015Smirl et al, , 2016Smirl et al, , 2018Smirl, Lucas, et al, 2014;Smirl, Tzeng, Monteleone, & Ainslie, 2014;. This methodological approach leads to greater reproducibility within the CA outcome measures (phase, absolute gain, and normalized gain) (Claassen et al, 2009;Smirl et al, 2015), which will enhance the interpretability and application of the findings related to the current investigation.…”
Section: Introductionmentioning
confidence: 99%